Vision of women’s freedom: a feminist study of selected writings by Rokeya Sakhawat Hossain - Sanjida, Sania (BRAC Univeristy, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2016.